Compost and biochar alter mycorrhization, tomato root exudation, and development of Fusarium oxysporum f. sp. lycopersici - Akhter, Adnan; Hage-Ahmed, Karin; Soja, Gerhard; Steinkellner, Siegrid (Frontiers in Plant Science, 2015)
Soil amendments like compost and biochar are known to affect soil properties, plant growth as well as soil borne plant pathogens. Complex interactions based on microbial activity and abiotic characteristics are supposed to be responsible for suppressive properties of certain substrates, however, the specific mechanisms of action are still widely unknown. In the present study, the main focus was on the development of the soil borne pathogen, Fusarium oxysporum f.sp. lycopersici (Fol) in tomato (Solanum lycopersicum L.) and changes in root exudates of tomato plants grown in different soil substrate compositions, such as compost (Comp) alone at application rate of 20% (v/v), and in combination with wood biochar (WB; made from beech wood chips) or green waste biochar (GWB; made from garden waste residues) at application rate of 3% (v/v), and/or with additional arbuscular mycorrhizal fungi (AMF). The association of GWB and AMF had a positive effect on tomato plants growth unlike to the plants grown in WB containing a soil substrate. The AMF root colonization was not enhanced by the addition of WB or GWB in the soil substrate, though a bio-protective effect of mycorrhization was evident in both biochar amended treatments against Fol. Compost and biochars altered root exudates differently, which is evident from variable response of in vitro growth and development of Fol. The microconidia germination was highest in root exudates from plants grown in the soil containing compost and GWB, whereas root exudates of plants from a substrate containing WB suppressed the mycelial growth and development of Fol. In conclusion, the plant growth response and disease suppression in biochar containing substrates with additional AMF was affected by the feedstock type. Moreover, application of compost and biochars in the soil influence the quality and composition of root exudates with respect to their effects on soil-dwelling fungi.